ANALYSIS OF CHEMICAL CONSTITUENTS OF ROCKY OUTCROPS IN SOLLARE, GULANI LOCAL GOVERNMENT AREA OF YOBE STATE, NIGERIA - WANAH, BALA BELLO; KORE, SALE ZAKAR (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2020)
This research work focused on analyzing the chemical composition of the rocky outcrops in Sollare, Gulani Local Government Area of Yobe State with the aim of determining the economic importance of the rocks. The field equipment used included GPS, prismatic compass, geographic hammer and polythene bags. Three (3) fairly sizeable pieces of rocks with fresh surfaces were prepared and collected one from each site as representative samples and taken to the laboratory for geochemical analysis. Preparation of the samples involved the use of analytical balance, weighing boat and aluminum press cups- Herzurg swing mill and Herzurg press machine. XRF (X-ray Fluorescence) analysis was carried out on the 3 samples at the Laboratory of Ashaka Cement Factory. Results of the analysis showed that the average percentage of Calcium Carbonates was 96.333%. Some of the chemical constituents of the 3 samples included silica (Si02 2.905%), aluminium oxides (Al2O3 1.937%), iron oxides (Fe2O3 1.359%), magnesium oxides (MgO2 0.660%) and potassium oxides (K2O, 0.115%). The outcrops covered an area of 45.56 km2. Analysis of interview responses on the cultural values attached to the rocky outcrops showed that there were no values attached to the rocks. For time and financial constraints, chemical analysis on other rock outcrops farther away from Sollare could not be carried out. With this result, it is believed that Companies could exploit the rocks for the production of cement and other valuable products. It is also recommended that some researchers should conduct some researches on those rocks, and on rocks elsewhere in Nigeria with a view of determining their chemical composition in order to establish their economic importance.